PENYELESAIAN PERMASALAHAN KLAIM SENGKETA TANAH EIGENDOM VERPONDING MELALUI HUKUM KONFLIK AGRARIA - Damianus Krismantoro (GoAcademica Research dan Publishing, 2019)
This research will be carried out with the aim of being able to find out how agrarian law sees and resolves problems in land ownership disputes on land that has Eigendom Verponding problems in Indonesia. This research is a normative juridical research, which places norms, laws and regulations, court decisions, agreements and doctrines as the main study and prioritizes secondary data as the main data. This study then found that in many cases of Eigendom Verponding land disputes which were taken over by the state, the legality process of land rights status became the main basis for the occurrence of Eigendom Verponding land conflicts which were caused, among others, the incomplete land registration process in Indonesia by the government or the land owner himself. Then the state apparatus often forcibly took over the land from the hands of people called development projects. Although the expropriation was based on the legislation on the abolition of privately owned lands, there was no process of providing adequate compensation as regulated in the provisions of the national agrarian law. Here there is a legal conflict with each other.